HOXD9 prioritization within developmental regulator-related genes suggests stage-adjusted prognostic relevance in hepatocellular carcinoma - Zhu, Junling; Tang, Xujie; Zhu, Qianru; Jiang, Sen (Translational Cancer Research, 2026)
Background: Prognostic stratification in hepatocellular carcinoma (HCC) remains difficult because standard staging systems do not fully capture the biological heterogeneity of the disease. We hypothesized that developmental regulators could provide a biologically relevant framework for prioritizing prognostic markers.Methods: RNA sequencing (RNA-seq) and clinical data from The Cancer Genome Atlas liver hepatocellular carcinoma (TCGA-LIHC) cohort were analyzed. Tumor vs. normal differential expression analysis was performed using differential expression analysis for sequence count data 2 (DESeq2). Developmental regulator-related candidate genes were prioritized through a stepwise framework integrating differential expression, clinicopathological association, Kaplan-Meier survival analysis, and Cox regression. A main prognostic model was constructed from the final independent factors and evaluated using a nomogram, calibration analysis, and time-dependent receiver operating characteristic (ROC) analysis. The incremental prognostic value of HOXD9 beyond pathologic stage was assessed using the likelihood ratio test, Harrell’s concordance index (C-index), bootstrap-based delta C-index analysis, and time-dependent area under the curve (AUC) comparison. External validation was performed in the LIRI-JP (Liver Cancer-RIKEN, Japan) cohort.Results: Among the screened developmental regulator-related genes, HOXD9 and MESP2 showed the most consistent signals across differential expression, clinicopathological association, and survival analyses. In multivariable Cox regression in the TCGA-LIHC cohort, only pathologic stage [hazard ratio (HR) =1.565, 95% confidence interval (CI): 1.266–1.935; P